Desperate Times? Recruiting students for your department - William Hoon (Academic Chairpersons Conference Proceedings, 2016)
This presentation will review how one department at a regional Midwest university has dealt with the pressure of recruiting students. While the number of high school students in our state has declined, our department numbers has remained steady. Initiatives and best practices on how to attract and communicate with prospective students will be discussed.
Keywords: Recruiting; enrollment; management; department culture